Assessment of the tourist climate index of southern Kazakhstan for the development of rural tourism (Journal of Geography and Environmental Management, 2021)
The variety of tourist and recreational resources allows you to develop different areas of tourism. For this purpose, a comprehensive work is being carried out to assess the tourist and recreational potential of the region. The development of rural tourism directly depends on the socio-economic conditions, the state of infrastructure and the attractiveness of a particular tourist region. Rural tourism can complement mass tourism in many countries, as well as be an innovative initiative in areas with a low level of tourism development. Currently, in foreign countries, rural tourism is developing with a high rhythm. Kazakhstan also has great opportunities for the development of this type of tourism. To determine the opportunities for the development of rural tourism in a particular territory, it is necessary to conduct a special tourist and recreational assessment. The article analyzes the climate index of Southern Kazakhstan to assess the climate potential of rural tourism development. According to the characteristics of the climate index, the dynamics of the climatic comfort of the region is revealed. Depending on the points of the tourist climate index, a map of Southern Kazakhstan is compiled. The results of the study allow us to identify the regions of Kazakhstan that are favorable from the point of view of climatic comfort. This is an important factor for tourists and directly for the development of rural tourism and is one of the most important stages of tourist and recreational assessment
Keywords: rural tourism, rural area, village, tourist and recreational potential, tourist climate index, effective temperature.